Crayfish shells-derived carbon dots as a fluorescence sensor for the selective detection of 4-nitrophenol. Issue 1 (31st December 2023) - Chen, Jiannan; Xia, Xiuhua; Li, Peizhen; Yu, Hang; Xie, Yunfei; Guo, Yahui; Yao, Weirong; Qian, He; Cheng, Yuliang
ABSTRACT: As a type of environmentally deleterious compound, 4-nitrophenol (4-NP) has become a global concern due to its extreme toxicity to aquatic organisms and humans. Herein, we used naturally available crayfish shells as precursors to prepare a new type of carbon dots (CDs) by the hydrothermal method. The as-synthesized CDs exhibited strong blue fluorescence emission which can be sensitively quenched by 4-NP through the static quenching effect because of the formation of a ground state complex between CDs and 4-NP. Accordingly, a facile and rapid fluorescence sensor was developed to detect 4-NP from 0 μM to 50 μM with a limit of detection (LOD) of 0.16 μM. Furthermore, the proposed sensor was successfully applied for the detection of 4-NP in fresh crayfish meat and aquatic water samples.